Subclinical Hypothyroidism and Functional Mobility in Older Adults - Simonsick, Eleanor M. (2009)
CONTEXT: Health risks associated with subclinical hypothyroidism in older adults are unclear. OBJECTIVE: To compare the functional mobility of seventy-year-olds by thyroid function categorized by thyroid stimulating hormone (TSH) level as euthyroid (0.4 mU/L< TSH <4.5 mU/L) or having mild (4.5 mU/L≥ TSH <7.0 mU/L) or moderate subclinical hypothyroidism (7.0 mU/L≤ TSH ≤20.0 mU/L with normal FT4) cross-sectionally and over two years. DESIGN, SETTING, AND PARTICIPANTS: 2,290 community residents participating in the Year 2 clinic visit (July 1998-June 1999) of the Health, Aging and Body Composition study with measured TSH, capacity to walk 20 meters unaided and not taking thyroid medication or having TSH levels consistent with hyper- or hypothyroidism. MAIN OUTCOME MEASURES: Self-reported and performance-based measures of mobility (usual and rapid gait speed and endurance walking ability) assessed at study baseline (Year 2) and two years later. RESULTS: In age- and sex-adjusted analyses the mild subclinical hypothyroid group demonstrated better mobility – faster usual and rapid gait speed (1.20 vs. 1.15 m/s and 1.65 vs. 1.56 m/s; p<.001) and higher percent with good cardiorespiratory fitness and reported walking ease (39.2 vs. 28.0 and 44.7 vs. 36.5; p<.001). After two years, persons with mild subclinical hypothyroidism experienced similar decline as the euthyroid, but maintained their mobility advantage. Persons with moderate subclinical hypothyroidism had similar mobility and decline as the euthyroid group. CONCLUSIONS: Generally well-functioning seventy-year-olds with subclinical hypothyroidism do not demonstrate increased risk of mobility problems and those with mild elevations in TSH show a slight functional advantage.